Microbial enhanced oil recovery (MEOR) by Pseudomonas sp. under laboratory conditions - Santos, Erick de Aquino; Cruz, Manoel Jerônimo Moreira; Oliveira, Eddy José Francisco de; Oliveira, Olivia Maria Cordeiro de; Queiroz, Antônio Fernando de Souza; Soares, Sarah Adriana Rocha; Lima, Danusia Ferreira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
The purpose of this work was to propose sustainable solutions for advanced oil recovery by evaluating the ability of the bacterium Pseudomonas sp. in the biotransformation of alkanes, in addition to determining strain growth patterns under extreme conditions. For this, the work was initially carried out under laboratory conditions, in which the crude oil was fractionated to obtain the saturated fraction used in the experiment. The bacterial tolerance to salinity and temperature was also tested to determine the experimental conditions and set up the experiment in regard to these parameters. Additionally, an experiment was performed to produce a biosurfactant through biostimulation. The biotransformation experiment consisted of a triplicate with treatment and a control. For treatments, Erlenmeyers flasks received 100 mL of broth containing the biosurfactant, 10 g (10%) of NaCl, 3% of the strain and 1% of the saturated fraction. Erlenmeyer flasks were incubated at 40 °C and 180 rpm for 18 days with periodic analysis. The results initially showed the bacteria exhibited better tolerance at a temperature of 40 °C, and there was no significant change for the different salinities, which was a nonlimiting parameter. For the final experiment, the bacterial growth analysed by Optical Density (OD). exhibited a low variation, in which the lowest point was in T18 with an absorbance of 0.115 and the highest point was in T6 with an absorbance of 0.149. In the qPCR analysis of the bacterial population, the pattern found was similar to the optical density results, with low variation; the lowest number of copies of the 16S rRNA gene (6.66x 103) was found in T0 and the highest number was found in T12 (7.86x 103). For biotransformation analysis, time 6 was observed to have the highest rate, with 54% oil recovery (C30), followed by 52% (C31) and 51% (C29).